Posterior or Single-stage Combined Anterior and Posterior Approach Decompression for Treating Complex Cervical Spondylotic Myelopathy Coincident Multilevel Anterior and Posterior Compression. Issue 10 (December 2017) - Zhou, Xiaoxiao; Cai, Pan; Li, Yuwei; Wang, Haijiao; Xia, Shengli; Wang, Xiuhui
Abstract : Study Design: A single-center, retrospective, longitudinal matched cohort clinical study of prospectively collected outcomes. Objective: To compare retrospectively the clinical outcomes and complications of the posterior approach laminoplasty and single-stage anterior approach laminoplasty combined with anterior cervical corpectomy and fusion and anterior cervical discectomy and fusion for treating patients with cervical spondylotic myelopathy coincident multilevel anterior and posterior compression, known as complex cervical spondylotic myelopathy (cCSM) here. Summary of Background Data: The optimal surgical management of this type of cCSM remains controversial. Methods: Sixty-seven patients with multilevel cCSM underwent decompression surgery from 1996 to 2007. Among these patients, 31 underwent a single-stage combined approach with decompression (combined approach group) and 36 underwent laminoplasty for posterior approach (posterior approach group). Average operative duration, operative estimated blood loss, surgical costs, and cervical alignment were measured. Results: Average operative duration, operative estimated blood loss, and surgical costs were significantly lower in the posterior approach group than those in the combined approach group ( P <0.001). Visual analog scale and modified Japanese Orthopedic Association scale were insignificantly different at each data collection period ( P >0.05). No statistical difference was observed in the preoperative Cobb angle ( P >0.05), whereas a significant statistical difference was observed for the postoperative Cobb angle ( P <0.05) and variation of Cobb angle ( P <0.05) between the 2 groups. The surgical incidences of complications were 22.2% and 48.4% in the posterior and combined approach groups ( P <0.05), respectively. Conclusions: For treating multilevel cCSM, both the posterior approach laminoplasty and single-stage combined approach led to significant neurological improvement and pain reduction in the majority of patients. Both approaches showed similar results in terms of decompression and neurological improvement. The posterior approach was superior to the combined approach in terms of surgical costs, surgical time, blood loss, and complication rate.